Oral Leisons in Cancer Patients Receiving Chemotherapeutic Treatment in Fauji Foundation Hospital (Medical Forum Monthly, 2021)
Objective: To establish an association between effects of chemo therapeutic treatment in oral cavity in cancer patients reported in Fauji Foundation Hospital.Study Design: Randomizes controlled trial studyPlace and Duration of Study: This study was conducted at the Fauji Foundation Hospital among dental students and patients from May to July 2019.Materials and Methods: Cross-sectional study was conducted in Fauji Foundation Hospital, Pakistan from 1st May to 24th July 2019. Sample size of 100 patients was examined for oral manifestations. They were undergoing various cycles of cancer chemotherapeutic treatment. Treatment included cycles of chemotherapy and radiation. The study included patients of various types of cancers including Squamous Cell Carcinoma, Carcinoma breast, non-Hodgkin’s lymphoma, chronic myeloid leukemia etc. A scale with end points NO ORAL DISCOMFORT to WORST IMAGINABLE ORAL DISCOMFORT was used. History taking and non-invasive intra oral examination was carried out to check for any lesions, ulcers, pigmentation, xerostomia, taste alterations etc. Data was analyzed using SPSS version 21.Results: This was an observational type of study that included patients suffering from various malignancies. Overall 100 patient’s data were collected for this study. Lesions were seen in 76% of patients, of which 65% patients reported with ulcerative lesions, 21% with white lesions and 13% other category lesions. The most common symptomatic finding included taste alteration seen in 94% of patients and 74% with xerostomiaConclusion: This study suggests that the patient’s quality of life is related to chemotherapy cycles. Patients undergoing chemotherapy reported milder symptoms than patients undergoing radiotherapy. Xerostomia and taste alterations were among most significant findings. Data showed a correspondence between oral manifestations and cancer chemotherapeutic treatment.